Mechanical anisotropy in pectin films - Joseph Robert Nastasi; Kit Ching Tam; Thu An Le; Chenghao Li; Vassilis Kontogiorgos (Carbohydrate Polymers, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

Reef fish assemblages show limited response to giant clam density and restocking - Nathan W. Price; Yan-Zhen Meng; Wen-Yuan Zhang; Jinn-Shing Weng; Ching-Min Yang; Kao-Sung Chen; Joseph Heard; Wei-Chen Tung; Yu-De Pei; Colin Kuo-Chang Wen (Regional Studies in Marine Science, 2026)

Blood heavy metals content and gut microbiota profile in immature and nesting wild green turtles (Chelonia mydas) - Ming She See; Xin Li Ching; Nurshazwani Razali; Intan Syazwina Asri; Maizah Mohd Abdullah; Joseph Bidai; Mohd Uzair Rusli; Nyuk Ling Ma (Marine Environmental Research, 2026)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

A Review of Atmospheric Micro/Nanoplastics: Insights into Source and Fate for Modelling Studies - Fei Jiang; Chengze Gao; Arthur W. H. Chan; David O. Topping; Hongliang Zhang; Weijun Li; Hugh Coe; Xiaohong Liu; Joseph Ching; Zhonghua Zheng (Current Pollution Reports, 2025)
Purpose of Review Micro/nanoplastics (MNPs), as emerging pollutants, have attracted increasing attention due to their potential adverse effects on human health, ecosystems, and climate. The rapid, turbulent, and large-scale nature of atmospheric transport facilitates both horizontal and vertical movement of MNPs over long distances within a short time, largely independent of topographical constraints, thereby accelerating their global cycle and exacerbating their impacts. Despite growing interest, our understanding of the atmospheric lifecycle of MNPs remains limited. This review aims to synthesise recent advances in understanding the atmospheric lifecycle of MNPs, including their emission sources, long-range transport characteristics, and driving mechanisms. It also evaluates the key sources of uncertainty—particularly those related to emission flux estimates—and provides corresponding recommendations for future research. Recent Findings Current research on the atmospheric processes of MNPs primarily relies on a combination of observational data and numerical modelling. Two major uncertainties in atmospheric micro/nanoplastic (AMNP) emissions persist: the wide variability in marine emission estimates, which span four orders of magnitude, and the unresolved question of whether terrestrial or marine sources are the dominant contributors to AMNP emissions. Furthermore, this review highlights critical factors driving these uncertainties, including limited data availability, inconsistencies in observational methodologies, oversimplified simulations, and gaps in understanding atmospheric cycling mechanisms. Additionally, variations in the particle size ranges targeted by different observational and modelling studies hinder cross-comparisons and model evaluations, representing another important source of uncertainty. Summary AMNP research is constrained by multiple uncertainties that hinder a comprehensive understanding of their emissions, transport, and fate. To address these issues, we call for establishing a global network of standardised observations, improving sampling and simulation practices, and incorporating artificial intelligence. These strategies will enhance our understanding of the complete atmospheric cycle of MNPs, paving the way for more effective environmental management and better-informed policy decisions.

Understanding tractography in edematous brain regions: challenges and solutions - Shin Tai Chong; Joseph Yuan-Mou Yang; Ching-Po Lin (Brain Structure and Function, 2025)

Blood and cloacal microbiome profile of captive green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricata): Water quality and conservation implications - Xin Li Ching; Syamsyahidah Samsol; Mohd Uzair Rusli; Mohamad Aqmal-Naser; Joseph Anak Bidai; Christian Sonne; Xin Wu; Nyuk Ling Ma (Chemosphere, 2025)

Carcinogenic air pollutants and breast cancer risk in the Arkansas rural community health study: A nested case-control study - Edgar T. Ellis; Sean G. Young; Rachel Carroll; Shelbie D. Stahr; Gail A. Runnells; Elizabeth A. Grasmuck; L. Joseph Su; Yong-Moon Mark Park; Ping-Ching Hsu (Environmental Pollution, 2025)

Cigarette smoking and prostate cancer aggressiveness among African and European American men - Edgar T. Ellis; Brian J. Fairman; Shelbie D. Stahr; Jeannette T. Bensen; James L. Mohler; Lixin Song; Eboneé N. Butler; L. Joseph Su; Ping-Ching Hsu (Cancer Causes & Control, 2024)
Purpose Smoking is a modifiable lifestyle factor that has not been established as a prostate cancer risk factor, nor emphasized in prostate cancer prevention. Studies have shown that African American (AA) smokers have a poorer cancer prognosis than European Americans (EAs), while having a lower prevalence of heavy smoking. We examined the relationship between cigarette smoking and prostate cancer aggressiveness and assessed racial differences in smoking habits on the probability of high-aggressive prostate cancer. Methods Using data from the North Carolina-Louisiana Prostate Cancer Project ( n = 1,279), prostate cancer aggressiveness was defined as high or low based on Gleason scores, serum prostate-specific antigen levels, and tumor stage. Cigarette smoking was categorized as current, former, or never smokers. Multivariable logistic regression was used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI). Results Self-reported current (OR = 1.99; 95% CI 1.30–3.06) smoking was associated with high-aggressive prostate cancer relative to never smokers. When stratified by self-reported race, the odds of having high-aggressive cancer increased among AA current (OR = 3.58; 95% CI 2.04–6.28) and former smokers (OR = 2.21; 95% CI 1.38–3.53) compared to AA never smokers, but the odds were diminished among the EA stratum ( P self-reported race x smoking status = 0.003). Conclusion Cigarette smoking is associated with prostate cancer aggressiveness, a relationship modulated by self-reported race. Future research is needed to investigate types of cigarettes smoked and metabolic differences that may be contributing to the racial disparities observed.

Improved resilience and proteostasis mediate longevity upon DAF-2 degradation in old age - Adrian Molière; Ji Young Cecilia Park; Anita Goyala; Elena M. Vayndorf; Bruce Zhang; Kuei Ching Hsiung; Yoonji Jung; Sujeong Kwon; Cyril Statzer; David Meyer; Richard Nguyen; Joseph Chadwick; et al. (GeroScience, 2024)
Little is known about the possibility of reversing age-related biological changes when they have already occurred. To explore this, we have characterized the effects of reducing insulin/IGF-1 signaling (IIS) during old age. Reduction of IIS throughout life slows age-related decline in diverse species, most strikingly in the nematode Caenorhabditis elegans . Here we show that even at advanced ages, auxin-induced degradation of DAF-2 in single tissues, including neurons and the intestine, is still able to markedly increase C. elegans lifespan. We describe how reversibility varies among senescent changes. While senescent pathologies that develop in mid-life were not reversed, there was a rejuvenation of the proteostasis network, manifesting as a restoration of the capacity to eliminate otherwise intractable protein aggregates that accumulate with age. Moreover, resistance to several stressors was restored. These results support several new conclusions. (1) Loss of resilience is not solely a consequence of pathologies that develop in earlier life. (2) Restoration of proteostasis and resilience by inhibiting IIS is a plausible cause of the increase in lifespan. And (3), most interestingly, some aspects of the age-related transition from resilience to frailty can be reversed to a certain extent. This raises the possibility that the effect of IIS and related pathways on resilience and frailty during aging in higher animals might possess some degree of reversibility.

Outcome-Based blind tests for leakage diagnosis in underground watermains by acoustic technologies - Wallace Wai-Lok Lai; Tom Chun-Wai Lau; Alex Yu-Ching Cheng; Panda Kai-Chun Liu; Joseph Wang-Chi Leung (Tunnelling and Underground Space Technology, 2023)

Metal-binding peptides and their potential to enhance the absorption and bioavailability of minerals - Tolulope Joshua Ashaolu; Chi Ching Lee; Joseph Opeolu Ashaolu; Hadi Pourjafar; Seid Mahdi Jafari (Food Chemistry, 2023)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Correction to: Micro‑climatic variations across Malawi have a greater influence on contamination of maize with aflatoxins than with fumonisins - Justin Temwani Ng’ambi; Joseph Atehnkeng; Maurice Monjerezi; Cosmo Ngongondo; Ephraim Vunain; Connel Ching’anda; Alejandro Ortega‑Beltran; Peter J. Cotty; Limbikani Matumba; R. Bandyopadhyay (Mycotoxin Research, 2023)

Micro-climatic variations across Malawi have a greater influence on contamination of maize with aflatoxins than with fumonisins - Justin Temwani Ng’ambi; Joseph Atehnkeng; Maurice Monjerezi; Cosmo Ngongondo; Ephraim Vunain; Connel Ching’anda; Alejandro Ortega-Beltran; Peter J. Cotty; Limbikani Matumba; R. Bandyopadhyay (Mycotoxin Research, 2023)
This study reports levels of aflatoxin and fumonisin in maize samples ( n = 1294) from all agroecological zones (AEZs) in Malawi. Most maize samples (> 75%) were contaminated with aflatoxins and 45% with fumonisins, which co-occurred in 38% of the samples. Total aflatoxins varied across the AEZs, according to mean annual temperature ( P < 0.05) of the AEZs. Samples from the lower Shire AEZ (median = 20.8 µg/kg) had higher levels of aflatoxins ( P < 0.05) than those from the other AEZs (median = 3.0 µg/kg). Additionally, the majority (75%) of the positive samples from the lower Shire AEZ had aflatoxin levels exceeding the EU regulatory limit (4 µg/kg), whereas 25%, 37%, and 39% of positive samples exceeded the threshold in the mid-elevation, Lake Shore and upper and middle Shire, and highlands AEZs, respectively. The lower Shire AEZ is characterised by higher mean temperatures throughout the year and low erratic rainfall. However, total fumonisins did not show significant variation across AEZs, but all positive samples exceeded 150 µg/kg, required for tolerable daily intake of 1.0 µg/kg body weight per day, established by the European Food Safety Authority Panel on Contaminants in the Food Chain. Therefore, results of this study suggest that contamination of maize with aflatoxin responds to micro-climate more than with fumonisins. In addition, the data will be useful to public health policy-makers and stakeholders to articulate and implement monitoring and mitigation programs.

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Preclinical Pharmacokinetics Study of R- and S-Enantiomers of the Histone Deacetylase Inhibitor, AR-42 (NSC 731438), in Rodents - Hao Cheng; Zhiliang Xie; William P. Jones; Xiaohui Tracey Wei; Zhongfa Liu; Dasheng Wang; Samuel K. Kulp; Jiang Wang; Christopher C. Coss; Ching-Shih Chen; Guido Marcucci; Ramiro Garzon; et al. (The AAPS Journal, 2016)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Changes in the choice of colorectal cancer screening tests in primary care settings from 7,845 prospectively collected surveys - Martin C. S. Wong; George K. John; Hoyee W. Hirai; Thomas Y. T. Lam; Arthur K. C. Luk; Jessica Y. L. Ching; Simon S. M. Ng; Francis K. L. Chan; Sian M. Griffiths; Joseph J. Y. Sung (Cancer Causes & Control, 2012)

Effect of Polysorbate 80 Quality on Photostability of a Monoclonal Antibody - Swita R. Singh; Jingming Zhang; Courtney O’Dell; Ming-Ching Hsieh; Joel Goldstein; Joseph Liu; Arvind Srivastava (AAPS PharmSciTech, 2012)

Early Paleozoic medium-pressure metamorphism in central Vietnam: evidence from SHRIMP U-Pb zircon ages - Tadashi Usuki; Ching-Ying Lan; Tzen-Fu Yui; Yoshiyuki Iizuka; Tich Van Vu; Tuan Anh Tran; Kazuaki Okamoto; Joseph L. Wooden; Juhn G. Liou (Geosciences Journal, 2009)

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection - Chu-Hui Chiang; Chun-Yee Lee; Ching-Hsien Wang; Fuh-Jyh Jan; Shih-Shun Lin; Tsung-Chi Chen; Joseph A. J. Raja; Shyi-Dong Yeh (European Journal of Plant Pathology, 2007)

Apoptosis and autoimmunity - Jeannine S. Navratil; Chau-Ching Liu; Joseph M. Ahearn (Immunologic Research, 2006)

Neocortical activation by electrical and chemical stimulation of the rat inferior colliculus: intra-collicular mapping and neuropharmacological characterization - Hans C. Dringenberg; Nermeen Yahia; Joseph Cirasuolo; Darren McKee; Min-Ching Kuo (Experimental Brain Research, 2004)